عزل وتشخيص بعض أنواع المكورات العنقودية المنتجة لرائحة الابط لعينة من طلبة كلية العلوم قسم البيئة والتموث في جامعة المثنى - Mohammed, Abeer (University of Thi-Qar Journal of Science, 2015)
This study included isolation and identification Staphylococcus spp. that cause armpit odor , 90 samples ( Skinswabs) were collected from students of the Faculty of Science, Department of Environment and Pollution in AlMuthanna University , for the period from (November 2014 until February 2015), and included 40 armpit samples for males and 50 armpit samples for females . It was alerted donors to stop the use of deodorant and inhibitors sweating before 24 hours of sample collection , then diagnosed samples and laboratory diagnostic results showed that emergence of 74 sample ( 30 males and 44 females ) is positive for the gram dye in the form grape clusters , belonging to the types of Staphylococcus spp. that cause armpit odor ,and then all isolates were subjected to the biochemical tests , the results have been obtained 46(62.2%) Staph. epidermidis , 18(24.3%) Staph. aureus, 7(9.5%) Staph. haemolyticus and 3(4.1%) Staph. saprophyticus .